Genetic variants in or near ADH1B and ADH1C affect susceptibility to alcohol dependence in a British and Irish population. (16th April 2014) - Way, Michael; McQuillin, Andrew; Saini, Jit; Ruparelia, Kush; Lydall, Gregory J.; Guerrini, Irene; Ball, David; Smith, Iain; Quadri, Giorgia; Thomson, Allan D.; Kasiakogia‐Worlley, Katherine; Cherian, Raquin; et al.
Abstract Certain single nucleotide polymorphisms (SNPs) in genes encoding alcohol dehydrogenase (ADH) enzymes confer a significant protective effect against alcohol dependence syndrome (ADS) in East Asian populations. Recently, attention has focused on the role of these SNPs in determining ADS risk in European populations. To further elucidate these associations, SNPs of interest in ADH1B, ADH1C and the ADH1B/1C intergenic region were genotyped in a British and Irish population (ADS cases n = 1076: controls n = 1027) to assess their relative contribution to ADS risk. A highly significant, protective association was observed between the minor allele of rs1229984 in ADH1B and ADS risk [allelic P = 8.4 × 10−6, odds ratio (OR) = 0.26, 95 percent confidence interval, 0.14, 0.49]. Significant associations were also observed between ADS risk and the ADH1B/1C intergenic variant, rs1789891 [allelic P = 7.2 × 10−5, OR = 1.4 (1.2, 1.6)] and three non‐synonymous SNPs rs698, rs1693482 and rs283413 in ADH1C. However, these associations were not completely independent; thus, while the ADH1B rs1229984 minor allele association was independent of those of the intergenic variant rs1789891 and the three ADH1C variants, the three ADH1C variants were not individually independent. In conclusion, the rare ADH1B rs1229984 mutation provides significant protection against ADS in this British and Irish population; other variants in the ADH gene cluster also alter ADS risk, although the strong linkage disequilibrium between SNPs at this location precluded clear identification of the variant(s) driving the associations.